A multicenter LArge retrospectIve daTabase on the personalization of stereotactic ABlative radiotherapy use in lung metastases from colon-rectal cancer: The LaIT-SABR study. (January 2022) - Nicosia, L.; Franceschini, D.; Perrone-Congedi, F.; Casamassima, F.; Gerardi, M.A.; Rigo, M.; Mazzola, R.; Perna, M.; Scotti, V.; Fodor, A.; Iurato, A.; Pasqualetti, F.; et al.
Highlights: SABR provides high rates of local control to lung oligometastases. Local control of colorectal lung metastases seems lower compared to other tumors. We identified predictive factors of SABR response and polymetastases development. Predictive factors of local control are BED ≥125 Gy and lesion diameter ≤20 mm. Having lesion >20 mm and 4–5 metastases predicted for a polymetastatic evolution. Abstract: Introduction: Stereotactic ablative radiotherapy (SABR) has been shown to increase survival in oligometastatic disease, but local control of colorectal metastases remains poor. We aimed to identify potential predictive factors of SBRT response through a multicenter large retrospective database and to investigate the progression to the polymetastatic disease (PMD). Material and methods: The study involved 23 centers, and was approved by the Ethical Committee (Prot. Negrar 2019-ZT). 1033 lung metastases were reported. Clinical and biological parameters were evaluated as predictive for freedom from local progression-free survival (FLP). Secondary end-point was the time to the polymetastatic conversion (tPMC). Results: Two-year FLP was 75.4%. Two-year FLP for lesions treated with a BED < 00 Gy, 100–124 Gy, and ≥125 Gy was 76.1%, 70.6%, and 94% ( p = 0.000). Two-year FLP for lesion measuring ≤10 mm, 10–20 mm, and >20 mm was 79.7%, 77.1%, and 66.6% ( p = 0.027). At the multivariate analysis a BED ≥125 Gy significantly reduced the risk of local progression (HR 0.24, 95%CI 0.11–0.51; p = 0.000). Median tPMC was 26.8 months. Lesions treated with BED ≥125 Gy reported a significantly longer tPMC as compared to lower BED. The median tPMC for patients treated to 1, 2–3 or 4–5 simultaneous oligometastases was 28.5, 25.4, and 9.8 months ( p = 0.035). Conclusion: The present is the largest series of lung colorectal metastases treated with SABR. The results support the use of SBRT in lung oligometastatic colorectal cancer patients as it might delay the transition to PMD or offer relatively long disease-free period in selected cases. Predictive factors were identified for treatment personalization.